Postinfectious Onset of Myasthenia Gravis in a COVID-19 Patient - Huber, Meret; Rogozinski, Sophia; Puppe, Wolfram; Framme, Carsten; Höglinger, Günter; Hufendiek, Karsten; Wegner, Florian (Frontiers in Neurology, 2020)
Objective: We report the case of a young woman with postinfectious onset of myasthenia gravis after COVID-19 with mild respiratory symptoms and anosmia/ageusia one month before admission to our neurological department. Methods: Patient data were derived from medical records of Hannover Medical School, Germany. Written informed consent was obtained from the patient. Results: The 21-year-old female patient presented with subacute, vertically shifted double vision evoked by right sided partial oculomotor paresis and ptosis. About four weeks earlier she had suffered from mild respiratory symptoms, aching limbs and head without fever, accompanied by anosmia/ageusia. During the persistence of the latter symptoms for around 10 days the patient had already noticed “tired eyes” and fluctuating double vision. Clinical assessment including a positive test with edrophonium chloride and increased acetylcholine receptor antibodies related the ocular manifestation etiologically to myasthenia gravis. Antibodies (IgA/IgG) against SARS-CoV-2 using three different serological tests (Abbott, DiaSorin, Euroimmun) were detected in serum suggesting this specific coronavirus as previously infectious agent in our patient. The myasthenic syndrome was treated successfully with intravenous immunoglobulins and oral pyridostigmine. Conclusion: This is the first case presentation of postinfectious myasthenia gravis as neurological complication in a COVID-19 patient.